Pengaruh Upah Minimum Regional (UMR) dan Jumlah Penduduk Terhadap Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan - Siti Nuridah; Rony Marthin Sitohang; Ririn Sri Puspitasari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
As Indonesian citizens, the community has the right to the entire contents of the land and buildings. The management of the land (land) and buildings is fully handed over to the state to fulfill the people's welfare. The state needs money to manage the land (land) and buildings. The costs required for this management come from state revenues, one of which comes from taxes. Therefore, taxpayers are expected to be aware of the taxes they pay. Judging from the research data, the Bekasi District Minimum Wage starts from 2017 to 2021 and continues to increase. The population in Bekasi Regency in 2017 decreased in 2018 and then increased from 2018 to 2021. Realization of Rural and Urban Land and Building Tax (PBB P2) in Bekasi Regency from 2017 to 2021 has increased. This study aims to determine the magnitude of the influence of the Regional Minimum Wage (UMR) and Population together on Rural and Urban Land and Building Tax Receipts recorded at the Bekasi District Government Office. The data analysis method used is descriptive analysis method and analytical method quantitative. There is an influence between the District Minimum Wage (UMK) and Total Population together on Rural and Urban Land and Building Tax Revenue at the Bekasi District Government Office because the calculated F value (305.933) is greater than the F table value (2.95) so that H1 is accepted. District Minimum Wage (UMK) and Total Population together have a very strong positive effect (r value of 0.956) and have a contribution of 95.6% influence on Land and Building Tax Receipts in Rural and Urban Bekasi District Government Offices. While the remaining 4.4% is influenced by other factors.